Change of home visit frequency by public health nurses predicts emergency escorts for psychiatric patients living in the community: A retrospective medical record review - Wu, Meng-Chieh; Hung, Chia-Chun; Fang, Su-Chen; Lee, Tony Szu-Hsien (Frontiers in Public Health, 2023)
Background Improper or insufficient treatment of mental health illness harms individuals, families, and society. When psychiatric treatment shifts from a hospital-based to a community-based health care system, risk management is essential to the provision of effective care. Objective We examine whether an upgrade in home visit frequency of psychiatric patients as identified by public health nurses can predict the subsequent need for emergency escort services for medical treatment. Design A 2-year retrospective medical record review. Setting(s) A district of New Taipei City in Taiwan. Participants A total of 425 patients with a diagnosed mental health illness cared for through home visits by public health nurses from January 2018 to December 2019. Methods We accessed the Ministry of Health and Welfare's psychiatric care management information system to identify a set of medical records, and analyzed these records using chi-square and regression analyses. Results The analyses indicated that the groups experiencing the greatest need for emergency escort services were: male, 35–49 years old, with a senior high school level of education, without a disability identification card, with a schizophrenia diagnosis, and had been reported by the nurse as having progressed to a serious level. Nurses' increased frequency of home visits (an indicator that the patient's overall condition was worsening) and nurses' reports of increased severity of problems were significant predictors of the need for emergency escort services. Conclusions The nurses' adjustment of visit frequency based on the results of the visit assessment predicts the need for emergency escort services for mental patients. The findings support not only the professional roles and functions of public health nurses, but also the importance of strengthening psychiatric health community support services.